THE INFLUENCE OF COMPANY SIZE, AUDIT COMMITTEE AND AUDIT OPINION ON AUDIT REPORT LAG REGISTERED IN BANKING COMPANIES FOR THE 2019-2021 PERIOD - Suryanti, Dwi; Alliyah, Siti (Jurnal Ilmiah Akuntansi Indonesia, 2024)
The interval between the financial report and the audit report is termed "audit report lag," and it measures how long an auditor takes to perform an audit. How long it takes the auditor to analyse the company's financial records may influence several decisions. To be useful, financial reports must be delivered quickly and accurately. This study examines 2019–2021 banking industry audit committee makeup, business size, and audit opinion delay correlations. The independent variables are audit committee, firm size, and audit opinion, and the dependent variable is audit report latency. Population includes all 2019–2021 Indonesia Stock Exchange (BEI) banks and financial institutions. The study used documentation and purposeful sampling to gather data. Data is analysed using multiple linear regression. The study indicated that audit committee, audit opinion, and business scale had small but noticeable negative effects on audit report lag. Audit opinion had a small but significant beneficial effect, while firm size had a huge negative effect.